"Ditch the white coats": What LGBTQ+ patients prefer in their primary care provider. Issue 1 (14th December 2022) - Broholm, Cindy; Lindell, Deborah; Trossello, Catherine; Lauren, James; Smith, Brittany; Harris, Alexander B.; Quinn Griffin, Mary T.; Radix, Asa
ABSTRACT: Background: Health disparities in lesbian, gay, bisexual, transgender, queer and other sexual and gender minority (LGBTQ+) individuals are well documented, and there is a dearth of primary care providers (PCPs) with the knowledge, skills, and attitudes to sensitively care for this diverse population. Purpose: The purpose of this research study was to ask LGBTQ+ patients what qualities they prefer in their PCP. The findings will be used to better prepare nurse practitioners (NPs) to care for this diverse community and inform the training of future NPs to provide patient-centered care to LGBTQ+ individuals. Methodology: In this qualitative descriptive study, four focus groups were conducted remotely between December 2020 and January 2021 with self-identified LGBTQ+ patients of an LGBTQ+ health center in the northeast. Thematic analysis of the data elicited codes, categories, and themes. Strategies were implemented to promote trustworthiness of the results. Results: Twenty-eight participants shared the qualities they value in their PCP. Analysis revealed four themes: "Ditch the white coats"; "Meet me where I am"; "The relationship is key"; and "Be knowledgeable about and comfortable with LGBTQ+ people and their health care needs." Conclusions: The focus groups elucidated important information on caring for the LGTBQ+ communities and insights into what NPs must do to provide patient-centered care to this diverse population. Implications: These findings can improve practice through a better understanding of LGBTQ+ patients' perspectives. Additionally, this study demonstrates the feasibility of directly asking our patients what they want in their health care provider.